Contamination of vineyard soils with fungicides: a review of environmental and toxicological aspects - Komárek, Michael; Čadková, Eva; Chrastný, Vladislav; Bordas, François; Bollinger, Jean-Claude (Environment international, 2010)
The contamination of agricultural soils with inorganic (Cu-based) and organic pesticides (including their residues) presents a major environmental and toxicological concern. This review summarizes available studies published on the contamination of vineyard soils throughout the world with Cu-based and synthetic organic fungicides. It focuses on the behavior of these contaminants in vineyard soils and the associated environmental and toxicological risks. The concentrations of Cu in soils exceed the legislative limits valid in the EU in the vast majority of the studied vineyards. Regarding the environmental and toxicological hazards associated with the extensive use of fungicides, the choice of fungicides should be performed carefully according to the physico-chemical properties of the soils and climatic and hydrogeological characteristics of the vine-growing regions.
Keywords: Fungicides, Industrial; víno; Pesticide Residues; Copper; Environmental Monitoring; Environmental Pollution; látky znečišťující půdu; Soil Pollutants; průmyslové fungicidy; Agriculture; půda; rezidua pesticidů; znečištění životního prostředí; Wine; měď; monitorování životního prostředí; zemědělství; Vitis; Soil